Pomoč medicinske sestre paru, ki pričakuje otroka - Skoberne, Mihaela (Obzornik zdravstvene nege, 1985)
The ways in which health workers can help future parents are objective description of the process of childbirth, instructions given to the husband who is to be with his wife during labour, and accounts of labour as experienced by other couples. Assistance to parents-to-be can only be provided by a nurse who has a constructive attitude towards the special role of the husband during labour and who is competent to make out and complement an individual health care programme, including the assistance of the husband, for each couple separately.